2018
DOI: 10.1111/peps.12286
|View full text |Cite
|
Sign up to set email alerts
|

Leaders and followers behaving badly: A meta‐analytic examination of curvilinear relationships between destructive leadership and followers’ workplace behaviors

Abstract: We draw from social psychological and resource-based theories to meta-analytically examine curvilinear relationships between destructive leadership and followers' workplace behaviors (i.e., job performance, organizational citizenship behaviors, and workplace deviance). Overall, our meta-analytic results demonstrate that relationships between destructive leadership and followers' workplace behaviors are essentially linear. The limited evidence of curvilinear relationships we did find supports the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 170 publications
1
73
0
2
Order By: Relevance
“…Instead, they are more likely to retaliate toward subordinates, often through destructive leadership. Destructive leadership takes many forms (Mackey et al, 2019), including abusive supervision (Tepper, 2000), incivility (Andersson & Pearson, 1999), undermining (Duffy et al, 2002), and aggression (Mitchell & Ambrose, 2007). Although being conceptually and operationally distinct in many ways, these constructs are related in that they capture forms of hostility perpetrated on subordinates by supervisors.…”
Section: Theoretical Foundations and Proposition Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they are more likely to retaliate toward subordinates, often through destructive leadership. Destructive leadership takes many forms (Mackey et al, 2019), including abusive supervision (Tepper, 2000), incivility (Andersson & Pearson, 1999), undermining (Duffy et al, 2002), and aggression (Mitchell & Ambrose, 2007). Although being conceptually and operationally distinct in many ways, these constructs are related in that they capture forms of hostility perpetrated on subordinates by supervisors.…”
Section: Theoretical Foundations and Proposition Developmentmentioning
confidence: 99%
“…Therefore, as shown in Figure 1, we extend prior work by shedding light on the cascading effects through which CEO DT personality impacts CEO–TMT exchange quality and, in turn, TMT members’ behaviors toward others. Specifically, we explain the adverse effects of CEO DT personality on two indicators of TMTs’ behavior—TMT destructive leadership (i.e., aggressive behaviors perpetrated on subordinates; Mackey et al, 2019) and TMT behavioral integration (i.e., TMT members’ collaborative engagement with one another; Carmeli, 2008; Simsek et al, 2005)—through the mediator of CEO–TMT exchange quality. We chose these two TMT behaviors because they capture TMT members’ treatment of their subordinates (i.e., TMT destructive leadership) and one another (i.e., TMT behavioral integration), which are the two primary groups within organizations against which TMT members can retaliate if they are mistreated by CEOs (because they cannot readily retaliate against the CEO due to power differentials).…”
mentioning
confidence: 99%
“…When employees are in a state of emotional exhaustion, it is difficult to ensure that their behavior can meet organizational expectations and system requirements. The accumulation of negative emotions, such as depression, decadence, fatigue, fear, and tension, will lead to decreased work motivation [ 23 ], or even absenteeism without reason, passive laziness, complaining, shirking responsibility and other behaviors [ 24 ]. Therefore, we propose that:…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%
“…Treadway, Shaughnessy, Breland, Yang, and Reeves (2013) found that workplace bullies with high levels of political skill were able to abuse coworkers and still receive high ratings of performance from their superiors. Likewise, even for leaders engaging in deviant leader behavior (Mackey, McAllister, Maher, & Wang, 2019), in a leadership study of midlevel managers, Harvey, Harris, Kacmar, Buckless, and Pescosolido (2014) found that when managers exhibited a high degree of political skill, employee perceptions of ethical leadership increased. However, the specific career implications of the deviant behaviors of dark personalities have not yet been empirically tested with reference to the combination of MACH, political skill, and tenure (Hirschfeld & Van Scotter, 2019).…”
Section: Political Skill Camouflages Machiavellianism: Career Role Pementioning
confidence: 99%